COMBINATION OF TAXOL WITH CARBOPLATIN IN THE TREATMENT OF PATIENTS WITH STAGES IIB-IV OVARIAN CANCER (FIRST MULTI-CENTER EXPERIENCE IN RUSSIA) - Zh. A. Martinova; I. V. Poddubnaya (ABV-press, 2014)
Taking into account the fact that the treatment of advanced ovarian cancer includes cytoreductive surgery and chemotherapy, it is important to take advantage of contemporary highly effective agents. In 2003 the Regional program for optimization of ovarian cancer treatment in Cancer centers of Russia was initiated: 100 patients from 22 Cancer dispensaries received combination chemotherapy with Taxol at the dose of 175 mg/m2 as 3 hours intravenous infusion, then Carboplatin at the dose to obtain AUC=5,0 (TCb scheme). As a result of this multi-center study, the effectiveness of TCb scheme as first line chemotherapy was confirmed. The scheme can be successfully implemented in Cancer Centers.